Poliploidi pada Ikan Mas (Cyprinus carpio L.) dengan Induksi Kejutan Panas Melalui Metode Perhitungan Jumlah Nukleolus - Savitri, Lisa; Setiawan, Arif Budi; Kasimo, Elfred Rinaldo; Juwita, Syntia Tanu; Antoro, Ester Lianawati; Wulansari, Ida Septika (Jurnal Veteriner; Vol 23 No 2 (2022)DO - 10.19087/jveteriner.2022.23.2.246, 2022)
Carp ( Cyprinus carpio  L.) is a widely cultivated Indonesian fishery commodity. The increasing demand for carp can be used as an opportunity to increase the production and income of farmers and fulfill the target of increasing the nutrition of the residents. The heat shock method is one method that is often used because the process is simpler than the others. Polyploidy analysis was carried out by counting the number of nucleoli in fish resulting from polyploidization. The results of the ploidization analysis of carp in this study showed that there were variations in the number (frequency) of nucleoli per cell in diploid, triploid, and tetraploid fish. The body size of tetraploid fish is larger than that of triploid fish. But triploid fish have a larger body size than diploid fish. Tetraploid goldfish have a larger size and nucleus and cell contents when compared to triploids, even more so with diploids. The more the number of cells causes the volume of cells in the body to increase, so that the body size or growth of the tetraploid carp is higher. The growth of organisms is also a process of multiplying the number of cells and increasing the volume of cells.